2015
DOI: 10.18632/oncotarget.5402
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandins induce early growth response 1 transcription factor mediated microsomal prostaglandin E2 synthase up-regulation for colorectal cancer progression

Abstract: Cyclooxygenase2 (COX2) has been associated with cell growth, invasiveness, tumor progression and metastasis of colorectal carcinomas. However, the downstream prostaglandin (PG)-PG receptor pathway involved in these effects is poorly characterized.We studied the PG-pathway in gene expression databases and we found that PTGS2 (prostaglandin G/H synthase and cyclooxygenase) and PTGES (prostaglandin E synthase) are co-expressed in human colorectal tumors. Moreover, we detected that COX2 and microsomal Prostaglandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
40
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 49 publications
4
40
0
Order By: Relevance
“…Previous reports support the present finding that PGE2 content is not changed upon decreasing COX-2 expression (31)(32)(33)(34)(35). A number of authors have demonstrated that in the Vhl ∆IE /Apc min / + intestinal tumor model, the production of PGE2 is not dependent on the levels of COX-2, since despite the blockage of COX-2 activity by nimesulide, the PGE2 content remained elevated, suggesting that the high PGE2 levels observed were due to an increase in mPGES1 expression (31,32).…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Previous reports support the present finding that PGE2 content is not changed upon decreasing COX-2 expression (31)(32)(33)(34)(35). A number of authors have demonstrated that in the Vhl ∆IE /Apc min / + intestinal tumor model, the production of PGE2 is not dependent on the levels of COX-2, since despite the blockage of COX-2 activity by nimesulide, the PGE2 content remained elevated, suggesting that the high PGE2 levels observed were due to an increase in mPGES1 expression (31,32).…”
supporting
confidence: 92%
“…The high expression of COX-2 and mPGES1 in their studies was explained by the direct activation of the promoter region of these two genes by hypoxia-inducible factor 2α (31), which associates hypoxia with the COX-2/mPGES1/PGE2 axis. In other report, PGs were able to induce mPGES1 expression through the activation of early growth response 1, implying a positive regulatory feedback between these components (33). In addition, mPGES1 has been observed to be increased in CRC tumor tissues and to correlate with a worse prognosis (34).…”
mentioning
confidence: 87%
“…In this regard, higher COX2 expression and PG levels have been detected in different tumors, which could explain the NSAIDs beneficial effects in cancer prevention and treatment (3). Prostaglandin F2 (PGF2) has been scarcely studied on cancer although it has been detected in several tumor types and cancer patient body fluids (4,5) and only recently has been mechanistically associated with cancer progression (6). PGF2 is produced through the combined action of cyclooxygenases (COX) and different isomerases, AKR1B1 and AKR1C3 among others, with scarce reports implicating them in cancer (7).…”
Section: Introductionmentioning
confidence: 99%
“…Increased contents of prostaglandins in ovarian tumors have been described in previous studies, possibly regulating cell proliferation and apoptosis in this specific tumor context (11), being PGE2 the most extensively studied in this context (10). However, we have found another PG with an emerging role in colon cancer progression (6) with a close relationship with the female reproductive system (14). PMEPA1 (also known as TMEPA1, transmembrane prostate androgen induced 1) gene was first identified as a highly androgen-inducible gene with abundant expression in prostatic epithelial cells, which eventually was described as a direct transcriptional target of the androgen receptor (AR) (15) but also being upregulated in renal cell carcinoma (16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation